Entrepreneurial interest and competency of selected public high school students in Quezon City - Lachica, Ariane Joy Chua (UP College of Home Economics, 2011)
The entrepreneurial preparedness and interest of public high school students and its relation to the home economics curriculum in the basic education curriculum inspired the researcher to conduct this study to: identify the perceived level of knowledge and skills among fourth year public high school students in relation to the entrepreneurial competencies; determine the respondents' interest and preparedness in engaging in entrepreneurial activities; and establish entrepreneurial competencies that should be given emphasis on the entrepreneurship curriculum of public high schools based on the results of the study. The respondents were 114 fourth year high school students of two public high schools in Quezon City who were chosen using random sampling. A survey questionnaire was administered to the respondents to measure their perceived competency and expressed preparedness and interest in entrepreneurship. The data collected was summarized and further analyzed using statistical analysis. Results show that the respondents: have 'average to above average' perceived competency in Entrepreneurship (DepEd TLE-Entrepreneurship curriculum and Personal Entrepreneurial Competencies) an in other skill-related topics; are interested in starting their own business; have enough knowledge and skills needed in entrepreneurship; and have the capability to find initial capital required in starting a business. Though the respondents rated themselves average to above average on all the learning competencies, results show that they need more exposure, training, practical application, and actual experiences on some of the learning competencies.